2001
DOI: 10.1046/j.1460-9592.2001.01113.x
|View full text |Cite
|
Sign up to set email alerts
|

Young at Heart: Understanding the Unique Psychosocial Adjustment of Young Implantable Cardioverter Defibrillator Recipients

Abstract: This article reviews the data related to psychosocial adjustment of young ICD recipients, postulates theories to explain potential adjustment difficulties to ICD therapy experienced by younger recipients, and suggests clinical management techniques for addressing the unique psychosocial concerns of young ICD recipients. Studies of young ICD recipients suggest that a wide range of psychosocial adjustment issues are prominent in the post-ICD implantation period and that the issues may be different from older ICD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0
3

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 80 publications
(57 citation statements)
references
References 16 publications
1
53
0
3
Order By: Relevance
“…Large studies, ideally utilizing structured clinical interviews to diagnose depressive and anxiety disorders, are needed to determine whether ICD indication and receipt of an ICD shock is associated with anxiety and depression. Moreover, anxiety and depression may differentially impact women, minorities, and young adults or elderly individuals [13,44,45]; thus, published research among these groups of ICD recipients is needed. Regardless, psychological intervention is warranted for patients with significant adjustment difficulties or psychiatric diagnoses [46][47][48].…”
Section: Implications and Conclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…Large studies, ideally utilizing structured clinical interviews to diagnose depressive and anxiety disorders, are needed to determine whether ICD indication and receipt of an ICD shock is associated with anxiety and depression. Moreover, anxiety and depression may differentially impact women, minorities, and young adults or elderly individuals [13,44,45]; thus, published research among these groups of ICD recipients is needed. Regardless, psychological intervention is warranted for patients with significant adjustment difficulties or psychiatric diagnoses [46][47][48].…”
Section: Implications and Conclusionmentioning
confidence: 99%
“…Reviews have reported that a significant proportion of ICD patients experience anxiety, depression or both [6][7][8][9], which may result from a number of factors, including concern about the nature and severity of their cardiac condition; apprehension about how the ICD works, looks, and feels; and the unpredictable nature of receiving ICD shocks [10][11][12][13]. One early systematic review from 1999 [6] reported substantial inter-study discrepancies in the rates of anxiety (24% to 88%) and depressive symptoms (24% to 33%), possibly due to the small sample sizes of studies reviewed and the different measures used.…”
Section: Introductionmentioning
confidence: 99%
“…However, our previous work indicated that health care providers, both cardiac physicians and nurses, do not feel comfortable addressing emotional issues, 28 with a minority of physicians and nurses rating issues such as depression (34 and 45%) and anxiety (46 and 55%) as "comfortable." We have detailed our treatment package in the peer-reviewed literature through a series of published case studies 20,29 as well as in our provider-based training materials. 7 The main tenet of this work is that discussing simple strategies with patients with ICDs and family members, such as normalizing stress/fear, reviewing coincidental antecedent behaviors to the shock and reassuring of their safety, and teaching warning signs of distress and avoidance behaviors, provides patients and families with some strategies to overcome shock.…”
Section: Specific Health Care Provider Interventionsmentioning
confidence: 99%
“…Szacuje się, że wśród populacji pacjentów z ICD chorzy młodzi -poniżej 50. roku życia stanowią około 10% [49]. Młody wiek należy do czynników ryzyka obniżonej jakości życia pacjentów z ICD [50].…”
Section: Wpływ Icd Na Qol Młodych Pacjentówunclassified